2006
DOI: 10.1002/chem.200600144
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Model of an α(2,6)‐Sialyl‐T Glycosylated MUC1 Eicosapeptide under Physiological Conditions

Abstract: To study the effect of O-glycosylation on the conformational propensities of a peptide backbone, a 20-residue peptide (GSTAPPAHGVTSAPDTRPAP) representing the full length tandem repeat sequence of the human mucin MUC1 and its analogue glycosylated with the (2,6)-sialyl-T antigen on Thr11, were prepared and investigated by NMR and molecular modeling. The peptides contain both the GVTSAP sequence, which is an effective substrate for GalNAc transferases, and the PDTRP fragment, a known epitope recognized by severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 58 publications
4
66
0
6
Order By: Relevance
“…Conformational studies by NMR complemented by light scattering measurements have indicated that deglycosylation of MUC1 results in a less extended and more globular structure (50). Similar studies using MUC1-related O-glycopeptides have shown that the carbohydrate moieties exert conformational effects (10)(11)(12), which may provide a rationale for differences in immune responses. Also, the use of glycosylated 1 led to the efficient activation of CTLs, which were able to recognize glycosylated and unglycosylated structures, with the former ones being preferred.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Conformational studies by NMR complemented by light scattering measurements have indicated that deglycosylation of MUC1 results in a less extended and more globular structure (50). Similar studies using MUC1-related O-glycopeptides have shown that the carbohydrate moieties exert conformational effects (10)(11)(12), which may provide a rationale for differences in immune responses. Also, the use of glycosylated 1 led to the efficient activation of CTLs, which were able to recognize glycosylated and unglycosylated structures, with the former ones being preferred.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, modification of the peptides with αGalNAc (Tn-antigen) led to stronger antibody binding. It has been proposed that the improved binding is due to saccharide induced conformational change of the peptide backbone (10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Boons et al [5] berichteten kürzlich über eine Vakzine, in der ein Glycoundecapeptid mit monosaccharidischer T N -Antigen-Seitenkette aus dem Tandem-Repeat von MUC1 direkt mit einem T-Zellepitop aus Poliovirus [6] und dem oben genannte TLR2-Agonisten verknüpft ist und durch die in Mäusen selektive Antiseren induziert wurden. In der Synthese dieser Vakzine wurde die selektive Entfernung der O-Acetylgruppen aus dem N-Acetylgalactosaminteil durch Umesterung mit Hydrazin in Methanol [7] Um den Einfluss des an basischen Gruppen reichen Lipopeptids auf die Konformation des MUC1-Glycopeptids [8] zu minimieren, wurde ein Oligoethylenglycol-Spacer zwischen TLR2-Ligand und B-Zellepitop eingebaut. Trägt die aktivierte Carbonsäureeinheit des Lipopeptids nur säurela-bile Schutzgruppen und ist das Glycopeptid im Kohlenhydrat bereits deblockiert, dann werden beim abschließenden Deblockieren die Palmitoylester nicht angegriffen, sodass eine reine, synthetische Vakzine erhalten wird.…”
unclassified
“…[23] Therefore, the development of antitumor vaccines requires nonimmunogenic linkers. As the specificity of the glycopeptide antigens obviously depends upon their conformation, [24] such linker structures should contain as few hydrogen-bond donors and acceptors as possible but should still promote water solubility. Alkyl thioethers are expected to fulfill these requirements.…”
mentioning
confidence: 99%